MANAJEMEN DISTRIBUSI DAN BUDAYA BERBAGI KONTEN NETLABEL (Studi Kasus Pengembangan Budaya Berbagi Dalam Distribusi Konten Musik Netlabel Di Indonesia) - , Arif Kusumawardhani; , Dr. Kuskrido Ambardi, M.A. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
In the world of media, changes marked by one active point become the sign of the emergence of a new era. The comunication sciences, as a learner of the media, need to conduct a study in order to keep intelligence and knowledge progressive and developing. The new media represented by cellualr telephones, games and the internet has become the point of transition from the old to the new era. In the music industry, the internet has become one of the points of transition from the physical era to the digital era, which subsequently leads to the culture of sharing. The internet label or Netlabel is a creative form of the internet literacy happening in society. It being born communally and developed from communities to unlimited space has become an alternative in the music industry that has existed for tens of years on the basis of copyright laws. This research focused on 6 netlabels that are part of Indonesian Netlabel Union, namely Yesnowave (Yogyakarta), Inmyroom (Jakarta), Hujan rekords (Bogor), Mindblasting (Kutorjo), Stoneage records (Tangerang) and Kanaltigapuluh (Malang). These netlabels established themselves as the representatives of netlabel development in Indonesia through the activities they had organized. Netlabel became one of the internet-based new media managed differently from traditional organizations. This research observed how the media management in the distribution of music through the culture of sharing was conducted by numerous netlabels in Indonesia as non-profit media and applied sharing culture. This research was performed using the descriptive qualitative research and case-study methods. The data were collected by observation, interviews, documentation and library study with purposive sampling technique applied in information selection. Observation on the 6 netlabels and 1 vessel chosen as subject matters showed that the dynamics of netlabels that journeyed from the pocket communities in each town are highly varied. Some were led by influential individuals, some were run communally. Furthermore, their managements were unstructured